PREPARING HUMAN SERVICE STUDENTS FOR LESBIAN, GAY, BISEXUAL, TRANSGENDER, AND QUEER (LGBTQ) AFFIRMATIVE PRACTICE IN AN ONLINE CLASSROOM SETTING - Gates, Trevor G (PUPIL: International Journal of Teaching, Education and Learning, 2018)
The motivation for this project was to examine the extent to which social work professional aspirations to prepare students for LGBTQ affirmative practice are operationalized within a particular classroom. Beliefs about lesbian, gay, bisexual, transgender, and queer (LGBTQ) issues rights have been a concern of human service organizations for the past several decades. Position statements from major professional human service organizations call for preparing students for affirmative practice with the LGBTQ communities. Human service accreditation standards note that diversities shape the human experience, and multiple intersecting identities, including race and ethnicity, class, gender, sexual orientation, and other identities inform how human service workers interact in the world. While these position statements represent definite commitments to appreciating LGBTQ diversity, whether these position statements lead to reduced stereotypes and affirmative practice with LGBTQ communities is unclear. The objective of this project was to explore the extent to which students’ beliefs about LGBTQ human rights changed over the course of a semester-long course. Using a mixed method design with a small class of social work students (n = 11) in the United States, this study found evidence of positive change in these students and that students were becoming more sensitive to the nuances of LGBTQ human rights. In this paper, I discuss my own experiences teaching about LGBTQ diversity in an online classroom. Challenges and opportunities for talking about sensitive issues such as LGBTQ issues are explored. Additionally, I examine lessons learned and make recommendations for future teaching about engaging people from LGBTQ identities.